Model‐based multi‐genotype characterization of drought stress target population of environments for the common bean in East Africa - Jha, Prakash Kumar; Beebe, Steve; Urban, Milan; Soto, Jonatan; Assefa, Teshale; Ramirez-Villegas, Julian (Wiley, 2025)
Efforts toward the development of common bean varieties that can perform better under the drought conditions in Eastern Africa are constrained by significant genotype–environment–management (G × E × M) interactions. To address this, an attempt was made previously to assess drought stress for Eastern Africa using the Target Population of Environments (TPE) approach, albeit by using a single cultivar. Here, we extend earlier TPE work with a larger sample of representative genotypes from East Africa including commercial and breeding lines. By using a larger genotype pool, we are able to (1) assess the extent to which TPEs identified vary across genotypes (i.e., generality of the TPEs) and (2) identify best‐performing genotypes for the various environments identified. To perform the analyses, we used the CROPGRO‐DRYBEAN cropping system model available in the Decision Support System for Agrotechnology Transfer (DSSAT) v4.7 calibrated and evaluated from field trials in Africa and Colombia with 10 genotypes. Our findings indicate that despite some level of genotype‐related variation, the dominant drought stress patterns, and their priorities—drought stress‐free conditions remain the dominant TPE, followed by terminal drought stress—remain unaltered. Moreover, we find that it is possible to reduce the extent and intensity of drought stress in various TPEs by adequately targeting genotypes from the pool considered herein. Importantly, the genotype characteristics for stress‐free, extreme terminal drought and moderate terminal drought stress are significantly different, confirming a differentiated breeding strategy is required between the TPEs. The findings from this study are useful for the modernization of the bean breeding programs in Africa.